Peningkatan Hasil Belajar Siswa Pada Pembelajaran IPA Dengan Menggunakan Pendekatan Inkuiri Di Sekolah Dasar - Yani, Mega Darma (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Through this research the writer approach inquiry in processes learning for there are many student. Obsevational stage is describe to plot, implement, and step-up study results. Type of this research is observational action braze, with use qualitative approaching and quantitative one consisting of two cycles. Observational student of class five and observational. Analisis’s result to learning planning on. Cycle is 83,85 experience step-ups on tehe second cycle, by derived 91,05. Result observinging to activity learns in learning on I, cycle is 84,09 experience step-ups on the second is 95,45. Result observinging to student activity in learning on I cycle is 78,13 experience step-ups on the second cycle, by derived 93,56. Learned result before perfom research average 73,60 on the second cycle, average 86,76. In short, the research action class uses approach inquiry could increase the student’s study result for exact sicience course. Kata kunci : hasil belajar, IPA, pendekatan, pembelajaran, dan inkuiri